The Mediating Role of Job Enthusiasm in the Model of Innovative Work Behaviors Based on Psychological Empowerment - kamran malekpour lapari; tayebeh dastanpoor; azam bakhtyarirenani (Allameh Tabataba'i University Press, 2022)
Due to the changing business environment, organizations have to consider innovation as a necessary prerequisite to increase their efficiency, productivity and sustainability. In this regard, they should pay more attention to increasing job enthusiasm, psychological empowerment, and stimulating innovative work behaviors. Therefore, this research was conducted with the aim of investigating the mediating role of job enthusiasm in the model of innovative work behaviors based on psychological empowerment. In terms of the objective, this research is part of applied research, and in terms of the data collection method, it is part of correlational quantitative research. The statistical population of this research was made up of all the male and female employees of the oil company in the central regions of Iran in 1401. Using simple random sampling, 345 people were selected as the research sample. The data of this research were collected using Spritzer and Mishra's (1995) Standard Questionnaires of Psychological Empowerment, Job Enthusiasm,      Salonava and Shoufeli (2001) and Innovative Work Behavior of Dijang and Denhartog (2010). According to the results of the research, the effect of psychological empowerment on job enthusiasm was 0.380, on innovative work behaviors was 0.297, and the effect of job enthusiasm on work behaviors was 0.352 (p<0.001). In addition, the results showed that psychological empowerment due to job enthusiasm has an effect on innovative work behaviors to the extent of 0.667 (p<0.05). Therefore, all variables have positively and directly influenced each other (p<0.001).